The Use of Pronoun in The Jakarta Post and Jakarta Globe - Miftakhur Rofi’ah (Universitas Gadjah Mada, 2013)
This research identified the use of pronoun in The Jakarta Post and Jakarta Globe. In particular, it aimed to investigate the frequency of pronoun and the strategy in using pronoun. The data used in this research were taken from 30 articles in the two newspapers. It used the pronoun theory in A Grammar of Contemporary English by Quirk, et al. (1985: 207˗228) which divide pronoun into five subclasses; central pronoun, relative pronoun, interrogative pronoun, demonstrative pronoun, and indefinite pronoun. Within each newspaper, the number of pronoun will be counted and compared. The strategy in using pronoun in both newspapers was also analyzed. The results of this research show that the frequency of pronoun in The Jakarta Post is less than in Jakarta Globe. Both newspapers have five similar strategies in using pronoun. Besides that, The Jakarta Post has three more different strategies, and Jakarta Globe has two more. These results conclude that each newspaper has similarity and dissimilarity in using pronoun.